The Effectiveness of Eye Movement Desensitization and Reprocessing Integrative Group Protocol with Adolescent Survivors of the Central Italy Earthquake - Maslovaric, Giada; Zaccagnino, Maria; Mezzaluna, Clarice; Perilli, Sava; Trivellato, Denis; Longo, Vittorio; Civilotti, Cristina (Frontiers in Psychology, 2017)
Earthquakes, which can cause widespread territorial and socio-economic destruction, are life-threatening, unexpected, unpredictable and uncontrollable events caused by the shaking of the surface of the earth. The psychological consequences, such as PTSD, anxiety, depression, and suicidal ideation, are well-known to clinicians and researchers. This study was conducted with the aim of evaluating the use of the Eye Movement Desensitization and Reprocessing (EMDR) Integrative Group Treatment Protocol (IGTP) on a sample of adolescents, after the earthquake in Central Italy on 24 August 2016. The objective of the EMDR intervention was to reduce PTSD symptoms. Before and after EMDR, specific assessment to find changes in PTSD symptoms was made using the IES-R (Impact of Event Scale Revised) and through the analyses of the Subjective Units of Disturbance (SUD). The EMDR treatment was given in three sessions (T1, T2, T3), each lasting 90 minutes, and the results at follow-up phase (T4) were also monitored. The results are very encouraging, showing significantly reduced PTSD symptoms in the majority of the subjects. The clinical implications and limitations will be discussed.